Acute hemolysis and methemoglobinemia secondary to fava beans ingestion in a patient with G6PD deficiency: A case report of a rare co-occurrence. Issue 47 (24th November 2021) - Al-Dubai, Husam; Al-Mashdali, Abdulrahman; Hailan, Yousef
Abstract: Rationale: Favism is a well-known cause of acute hemolytic anemia. Rarely, methemoglobinemia can also happen because of fava bean ingestion in patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency. Few cases with this co-occurrence have been reported in the literature. Patient concerns: We report a case of a 47-year-old patient who presented with jaundice that started 2 days after eating fava beans. Diagnoses: Laboratory investigations revealed anemia with evidence of hemolysis (high reticulocytes count, high indirect bilirubin, bite cells in peripheral smear). Blood gases showed high methemoglobin level. Reduced level of G6PD enzyme confirmed the diagnosis of G6PD deficiency. Intervention: The patient was kept on supplemental oxygen. He was counselled to avoid food and drugs that can cause acute hemolysis. Outcomes: Oxygen saturation improved gradually. The patient was discharged without any complications after 2 days. Lessons: Patients with G6PD deficiency can develop both acute hemolytic anemia and methemoglobinemia secondary to fava beans ingestion. These patients should not receive methylene blue to avoid worsening hemolysis.